Modified Glasgow prognostic score predicts perioperative adverse events in elderly patients undergoing hip fracture surgery (Annals of Medical Research, 2021)
Aim: The association between modified Glasgow prognostic score (mGPS) and prognosis in patients undergoing hip fracture surgery (HFS) has not been studied. Therefore, we aimed to evaluate the predictive value of mGPS in outcomes of patients undergoing HFS..Material and Methods: A total of 301 adult patients aged ≥ 65 years, undergoing HFS were included in this retrospective study. The mGPS was scored according to C-reactive protein (CRP) and albumin levels at enrolment. Patients with both elevated CRP (>1 mg/dL) and hypoalbuminemia (3.5 g/dL) are given mGPS of 2, patients with serum CRP ≤ 1 g/dL with or without hypoalbuminemia received scores of 0. Patients with only elevated CRP levels received mGPS of 1. Primary outcome of the study was major perioperative adverse medical events defined as cardiovascular and noncardiovascular complications.Results: A total of 38 patients (12.6%) experienced perioperative adverse medical events. Compared to patients without perioperative complications, patients with adverse events were more likely to have higher mGPS levels prior to surgert. Multivariate analysis showed that higher mGPS at presentation was an independent predictor of perioperative adverse medical events in patients undergoing HFS. Conclusion: This is the first study which demonstrates that mGPS is a predictor of adverse events in patients with undergoing HFS.
Keywords: Modified glasgow prognostic score; hip fracture; surgery